2017
DOI: 10.1186/s12985-017-0794-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-2 enhancer binding factor 2 interacts with the nsp9 or nsp2 of porcine reproductive and respiratory syndrome virus and exerts negatively regulatory effect on the viral replication

Abstract: BackgroundPorcine reproductive and respiratory syndrome virus (PRRSV) causes reproductive failures in sows and respiratory diseases in growing pigs, resulting in huge economic loss for the pig production worldwide. The nonstructural protein 9 (nsp9) and nonstructural protein 2 (nsp2) of PRRSV are known to play important roles in viral replication. Cellular interleukin-2 enhancer binding factor 2 (ILF2) participates in many cellular pathways and involves in life cycle of some viruses. In the present study, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 68 publications
5
15
0
Order By: Relevance
“…In this study, we initially show that ILF2 downregulates EV71 TCID50 and attenuates EV71 PFU, thereby repressing EV71 infection. Although this result is similar to previous reports showing that ILF2 regulates the replication of other viruses [28][29][30][31][32][33], this is the first study providing evidence that ILF2 represses EV71 infection. And although ILF2 plays critical roles in the repression of viral infection, the mechanism by which virus antagonizes ILF2-mediated antiviral effects was unknown until this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, we initially show that ILF2 downregulates EV71 TCID50 and attenuates EV71 PFU, thereby repressing EV71 infection. Although this result is similar to previous reports showing that ILF2 regulates the replication of other viruses [28][29][30][31][32][33], this is the first study providing evidence that ILF2 represses EV71 infection. And although ILF2 plays critical roles in the repression of viral infection, the mechanism by which virus antagonizes ILF2-mediated antiviral effects was unknown until this study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, 2B interacted with ILF2 ( Figure 4B), and ILF2 associated with 2B ( Figure 4C) in HEK293T cells, confirming the interaction between 2B and ILF2. Since 2B distributes in the cytoplasm [8] while ILF2 mainly locates in the nucleus [33], we next determined whether 2B colocalizes with ILF2 in HEK293T cells. A laser scanning confocal microscope showed that 2B (green) alone was mainly localized in the cytoplasm ( Figure 4D, top panels), and that ILF2 (red) alone was strongly distributed in the nucleus ( Figure 4D, middle panels); however, in the presence of both proteins, 2B and the majority of ILF2 were colocalized in the cytoplasm to form spots ( Figure 4D, bottom panels).…”
Section: Ev71 2b Interacts and Colocalizes With Ilf2 In The Cytoplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, interaction between Nsp9 and cellular annexin A2, retinoblastoma protein (pRb), DDX5 positively regulates the replication of PRRSV in vitro, demonstrating that PRRSV heavily relies on host cellular proteins to complete life cycle (Dong et al, 2014;Li et al, 2014a;Zhao et al, 2015). On the other hand, recent literature indicated that the interaction of Nsp9 with SUMO E2 conjugating enzyme Ubc9 and cellular protein interleukin-2 enhancer binding factor 2 (ILF2) through its RdRp domain resulted in a significantly decrease of virus titers, indicating that cells utilize host antiviral factors as defense mechanisms to limit PRRSV infection Wen et al, 2017). Altogether, these results provide insights into the complex interactions of PRRSV RdRp with the host proteome.…”
Section: Discussionmentioning
confidence: 99%
“…PRRSV nsp-specific antibodies. The mouse MAbs specific for PRRSV nsp1␤, nsp2 (E3G11), nsp4, nsp9, nsp10 (4D9), and nsp11 (3F9) were prepared in our laboratory and have been reported previously (72)(73)(74)(75)(76). Mouse anti-nsp12 MAb (1E5) was kindly provided by Changjiang Weng (Harbin Veterinary Research Institute) (57).…”
Section: Methodsmentioning
confidence: 99%